The livelihood dependency of Khasia community on betel leaf cultivation at Lawachara National park, Moulavibazar - Riadh, Sayeed Mahmud (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2008.